2020
DOI: 10.5194/cp-2020-108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate, cryosphere and carbon cycle controls on Southeast Atlantic orbital-scale carbonate deposition since the Oligocene (30–0 Ma)

Abstract: Abstract. The evolution of the Cenozoic Icehouse over the past 30 million years (Myr) from a unipolar to a bipolar world is broadly known; however, the exact development of orbital-scale climate variability is less well understood. Highly resolved records of carbonate (CaCO3) content provide insight into the evolution of regional and global climate, cryosphere and carbon cycle dynamics. Here, we generate the first Southeast Atlantic CaCO3 content record spanning the last 30 Myr, derived from X-ray fluorescence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…To further demonstrate the complexity of PP patterns, differential biogenic sedimentation has in some cases been reported even within small distances in the same basin. For example, ODP Site 1085 shows a rebound in CMAR after 3 Ma while the biogenic bloom seems to have persisted at Site 1264 until 3 Ma 27 .…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the complexity of PP patterns, differential biogenic sedimentation has in some cases been reported even within small distances in the same basin. For example, ODP Site 1085 shows a rebound in CMAR after 3 Ma while the biogenic bloom seems to have persisted at Site 1264 until 3 Ma 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The late Miocene onset of the SHS is coeval with many important climatic and oceanographic events, including the LMCIS, establishment of "modern" intermediate waters (Hodell & Venz-Curtis, 2006) and simultaneous peaks in carbonate production between the eastern Pacific and the South Atlantic (Drury et al, 2021). Our study demonstrates that TL turned on at 7 Ma, and therewith provides a new piece of the cause-and-effect chain shaping the major transformation of oceans and climate at that time.…”
Section: Discussionmentioning
confidence: 64%
“…Increases in the MAR of biogenic components (CaCO3, opal, organic carbon, phosphorus) between ~9 and 4 Ma have been measured in sediments from the Pacific, Indian and Atlantic Oceans (Farrell et al, 1995;Lyle and Baldauf, 2015;Van Andel et al, 1975;Grant and Dickens, 2002;Delaney and 525 Filippelli, 1994;Hermoyian and Owen, 2001;Dickens and Owen, 1999;Drury et al, 2020). This period of increased biogenic sedimentation, supported by independent paleoproductivity proxies (e.g., Diester Haass et al, 2005), is thought to reflect higher biological productivity and was dubbed the "biogenic bloom" by Farrell et al (1995).…”
Section: Late Miocene Sedimentation Patterns In the Southern Bay Of Bengalmentioning
confidence: 96%
“…S3b). 405-kyr modulation of the ocean carbon cycle, primarily recorded in carbonate content and benthic δ 13 C records (Herbert, 1997;Drury et al, 2020;De Vleeschouwer et al, 2020;Westerhold et al, 2020;Pälike et al, 2012;640 Paillard, 2017;Holbourn et al, 2007) but also in productivity and monsoon-related dust records (Rickaby et al, 2007;Wang et al, 2010), has been observed throughout the Cenozoic and Mesozoic sedimentary record. In middle Miocene records, poor carbonate preservation noted during eccentricity maxima is interpreted as indicating transient shoaling of the carbonate compensation depth (Holbourn et al, 2007;Flower and Kennett, 1994).…”
mentioning
confidence: 99%